A Thermally Activated Delayed Fluorescence Green OLED with 4500 h Lifetime and 20% External Quantum Efficiency by Optimizing the Emission Zone using a Single-Emission Spectrum Technique - Mac Ciarnáin, Rossa (Advanced materials (Deerfield Beach, Fla.), 2022)
© 2022 The Authors. Advanced Materials published by Wiley-VCH GmbH.